THU0560 PRIMARY CARE PHYSICIAN PERSPECTIVES ON DELAYS IN DIAGNOSIS OF AXIAL SPONDYLOARTHRITIS: A QUALITATIVE STUDY. (2nd June 2020) - Liu, S. H.; Lapane, K.; Shridharmurthy, D.; Khan, S.; Ferrucci, K.; Dubé, C.; Yi, E.; Kay, J.
Abstract : Background: The average delay in diagnosis for patients with any form of spondyloarthritis (SpA) ranges from 7 to 10 years [1–5]. In axial spondyloarthritis (axSpA), a subgroup of SpA, it is 5 to 14 years [4, 6, 7]. Factors that contribute to this delay include the lack of diagnostic criteria for axSpA and the difficulty in distinguishing inflammatory back pain (IBP), a key symptom of axSpA, from other highly prevalent forms of low back pain [8–10]. This impedes timely referral of these patients to rheumatologic care and initiation of appropriate treatment. Objectives: Describe understanding of, attitudes towards, and practices regarding axSpA among primary care physicians. Methods: We recruited 18 primary care physicians practicing in the United States as part of a larger qualitative study: the Sp ondyloA rthritis S creening and E arly D etection (SpA-SED) Study. We used purposive sampling with a goal of including an equal number of family medicine and internal medicine physicians who were balanced by gender. Physicians provided informed consent to participate in an in-depth interview (up to 60 minutes), conducted in person (n = 3) or over the phone (n = 15), between February and May 2019. The interview guide was developed by a multidisciplinary team, with input from rheumatologists. Topics included the physicians' approaches to evaluating back pain, their awareness about axSpA, their differential diagnosis of axSpA, the laboratory tests and imaging studies ordered when axSpA is suspected, their referral patterns for patients with presumed axSpA, their thoughts about factors contributing to diagnostic delay in axSpA, and their opinions about an Inflammatory Back Pain Assessment – ASAS criteria screening tool [5]. Results: Barriers to early diagnosis included patient factors (eg, multiple complaints, back pain not being the chief complaint), disease characteristics (eg, slow rate of disease progression), physician characteristics (eg, lack of rapport between patients and their primary care physicians), and structural/system issues (eg, lack of time). Most physicians reported that they would perform laboratory tests before referring a patient to a rheumatologist. Conclusion: Primary care physicians were surprised to learn of the average delay to axSpA diagnosis, considered that this lengthy delay was problematic, and agreed that improvements are needed in screening for and early detection of axSpA. Physicians believed that there would be a role for using a screening tool in the primary care setting to improve diagnostic delay, but that evidence to support its implementation is needed. References: [1]Dougados M et al. Arthritis Rheum. 1991;34:1218–27. [2]Amor B et al. Rev Rhum Mal Osteoartic. 1990;57:85–9. [3]van der Linden S et al. Arthritis Rheum. 1984;27:361–8. [4]Deodhar A et al. Arthritis Rheumatol. 2016;68:1669–76. [5]Sieper J et al. Ann Rheum Dis. 2009;68:784–8. [6]Sykes MP et al. Rheumatology (Oxford). 2015;54:2283–4. [7]Redeker I et al. Rheumatology (Oxford). 2019;58:1634–8. [8]Strand V et al. Mayo Clin Proc. 2017;92:555–64. [9]Proft F et al. Ther Adv Musculoskelet Dis . 2018;10:129–39. [10]Bohn R et al. Clin Exp Rheumatol. 2018;36: 263–74. Acknowledgments: We thank the participants for sharing their insights as part of this study. This abstract was written using data from a research study originally funded by Novartis (Principal Investigator: Shao-Hsien Liu, Co-Investigators: Jonathan Kay, Kate Lapane, Catherine Dubé). Disclosure of Interests: Shao-Hsien Liu Grant/research support from: Novartis Pharmaceuticals Corporation, Kate Lapane Grant/research support from: Novartis Pharmaceuticals Corporation, Divya Shridharmurthy Grant/research support from: Novartis Pharmaceuticals Corporation, Sara Khan Grant/research support from: Novartis Pharmaceuticals Corporation, Katarina Ferrucci Grant/research support from: Novartis Pharmaceuticals Corporation, Catherine Dubé Grant/research support from: Novartis Pharmaceuticals Corporation, Esther Yi Employee of: Novartis Pharmaceuticals Corporation, Jonathan Kay Grant/research support from: Gilead Sciences, Inc., Pfizer, Novartis Pharmaceuticals Corporation, Consultant of: Alvotech Suisse AG; Arena Pharmaceuticals, Inc.; Boehringer Ingelheim GmbH; Celltrion Healthcare Co. Ltd.; Merck Sharp & Dohme Corp.; Mylan Inc.; Novartis AG; Samsung Bioepis; Sandoz, Inc; UCB, Inc.